Water Quality Of Shrimp Pond Water During Harvesting - Ling, Teck Yee; Dunging, Buda; Nyanti, L.; Norhadi, Ismail; Emang, Justin Jok Jau (Universiti Malaysia Sarawak, 2013)
Shrimp farming is an important source of revenue for Sarawak. Shrimp farms are usually located at the estuary utilizing brackish water for the growth of shrimps. Due to the excess fE~ed and feces accumulation over the culture period, pond water had to be drained and the pond bottom cleaned during harvesting before the next cycle of culture could begin. It is important to study the quality of the pond water during discharge so that the effluent can be properly managed and nutrient recovered. This study was conducted in a commercial shrimp farm whereby water quality of the effluent was monitored in the outflow drain during harvesting. Results show that turbidity increased from 51 to 92 NTU during draining. Dissolved oxygen was below the minimum recommended for aquatic organism (S mg/L). Mean total ammonia-nitrogen exceeded 1 mg/L and ortho-phosphorus was 0.06 mg/L. The final portion of the effluent water was the highest in turbidity, nitrate-N, ammonia-nitrogen and ortho-phosphorus. It is recommended that nutrients in the effluent be recovered to avoid polluting the environment and replenish the depleting supply from natural source.